Interpreting Giambattista Vico for a new psychological science: Towards a semiotic imaginative approach. (December 2019) - Pern, Tuuli
Giambattista Vico is a visionary author whose work has ties to most human and social sciences. How to transform these ties from mere implications to explicit applicable principles for a new methodology in psychology and other human sciences? As an answer this article analyses from the point of view of semiotics the ideas set forth by different authors in the book 'Giambattista Vico and the new psychological science'. From the analysis emerges a set of methodological principles rooted in the ideas of Vico. Cultural psychology and semiotics provide the human sciences with a methodology that enables the researcher to recognise and preserve the otherness of its subject – and still have access to it. The key principles of this methodology are: awareness of the nature of human Umwelt (rootedness in bodily being and practical needs); the heterogeneity of sign systems and the limits of their translatability; historic, social and processual nature of human phenomena and last but not least: putting human rational thought in a context – of the human body, feeling and imagination.